Pelatihan Growth Mindset dan Jiwa Kompetitif melalui Permainan Edukatif untuk Mempersiapkan Pelajar Berdaya Saing Tinggi - Zakaria, Wan Abbas; Buhani, Buhani; Riniarti, Melya; Sumadi, Sumadi; Priyambodo, Priyambodo; Permatasari, Nindy (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2025)
Strengthening the competitive character of youth is a strategic step toward Indonesia Emas 2045. This article describes a community service model conducted at SMA Negeri 1 Karya Penggawa, Pesisir Barat, Lampung, aimed at fostering students’ competitive spirit. A participatory approach was implemented through motivational talks, interactive games based on experiential learning, and evaluative interviews, involving 78 students from grades X to XII. The motivational sessions raised awareness of the importance of a growth mindset and healthy competition. Games encouraged courage, teamwork, and emotional resilience. Interviews revealed changes in perception and increased motivation. This experiential model proves effective in developing a competitive character and is suitable for replication, especially in underdeveloped areas, to promote globally competitive Pancasila students.